Pulmonary Rehabilitation After Total Laryngectomy: A Multicenter Time-Series Clinical Trial Evaluating the Provox XtraHME in HME-Naïve Patients. (September 2015) - Parrilla, Claudio; Minni, Antonio; Bogaardt, Hans; Macri, Gian Franco; Battista, Mariapina; Roukos, Raymond; Pandolfini, Manlio; Ruoppolo, Giovanni; Paludetti, Gaetano; D'Alatri, Lucia; de Vincentiis, Marco
Background: Both the immediate beneficial physiological changes in a laboratory setting and the long-term clinical outcomes of heat and moisture exchanger (HME) use are well described. So far, there has not been any research published that provides detailed insight in the pattern of changes in both respiratory function and patients' experiences with HMEs in the first weeks of use. Methods: A multicenter time-series study design with a 2-week double baseline period. All patients used the XtraHME for 12 weeks afterward. Data were collected 2 weeks, 6 weeks, and 12 weeks after the start of HME use. Results: Data of 30 patients were analyzed. Pulmonary symptoms decreased significantly during the 12 weeks of HME use. After 2 weeks, a significant decrease in daily coughs and daily forced expectorations was seen. The general quality of life showed a significant increase throughout the study. More general physical complaints also significantly decreased with HME use. Patient satisfaction with the HME was high. Conclusions: This study shows that there is a significant influence of the XtraHME on pulmonary status that can already be observed after 2 weeks of using the XtraHME and continues to improve further after 6 weeks of XtraHME use.